2017
DOI: 10.1007/s13595-016-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

Forward selection in a maritime pine polycross progeny trial using pedigree reconstruction

Abstract: & Key message Molecular markers were used for paternity recovery in a maritime pine (Pinus pinaster Ait.) polycross trial, facilitating forward selection. Different breeding strategies for seed orchard establishment were evaluated by comparing genetic gains and diversity. This work opens up new perspectives in maritime pine breeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The use of genetic markers to recover paternity identity as a means of improving the accuracy of forward selections' breeding values and to better manage inbreeding was first proposed by Lambeth et al (2001) for tree breeding applications. Following paternity recovery in a maritime pine polycross progeny test, Vidal et al (2017) found slightly higher genetic gains for forward selection than for backward selection with equal constraints on genetic diversity. We propose that the additional level of information provided by the genomic relationship matrix and the potentially enhanced accuracy of offspring's genetic values obtained with GS models may further improve genetic gains in forward selection.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The use of genetic markers to recover paternity identity as a means of improving the accuracy of forward selections' breeding values and to better manage inbreeding was first proposed by Lambeth et al (2001) for tree breeding applications. Following paternity recovery in a maritime pine polycross progeny test, Vidal et al (2017) found slightly higher genetic gains for forward selection than for backward selection with equal constraints on genetic diversity. We propose that the additional level of information provided by the genomic relationship matrix and the potentially enhanced accuracy of offspring's genetic values obtained with GS models may further improve genetic gains in forward selection.…”
Section: Introductionmentioning
confidence: 90%
“…Polycross mating has since been advocated as a cost-effective approach for forward selection (e.g. Doerksen and Herbinger 2010;Vidal et al 2017). The main disadvantage of the polycross was the lack of pedigree tracing and inbreeding control that can nowadays be overcome by using genetic markers for pedigree reconstruction (Bouffier et al 2019) or by using the genomic relationship matrix in GS models.…”
Section: Polycross Mating Integrates Well Into Forward Gsmentioning
confidence: 99%
“…It occurs in animal species such as fish and pigs, in which the evaluation of sib performance is largely applied and allows to increase selection accuracy (Sonesson and Meuwissen, 2009;Tribout, 2011;Robledo et al, 2018). A related approach could be interesting for forest trees (Plomion et al, 2016) or forage plants when polycrosses (crosses using a mixture of pollens) are implemented: GS allows the redrawing of pedigrees, on the basis of data from fathers in particular, thus increasing the accuracy of selection (Riday, 2011;Vidal et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, simulations using the POPSIM software 84 in a Pinus pinaster improvement program, which was designed to maximize both gain and genetic diversity, generated a strategy of performing 150 controlled-crosses to obtain 100 progeny per cross as the most effective approach, but also the most time-consuming approach 18 . As an alternative, the option of using a polycross mating design together with paternity recovery using genotyping, is emerging as the preferred strategy to increase gain, and retain the desired effective population size with only a small decrease in male contributions, thereby allowing tree improvement programs to advance more quickly 17 , 18 , 80 , 85 , 86 . Although our data does not address the advantages of using a polycross directly, understanding the options and impact of different breeding strategies is critical to the rapid advancement of any long-lived tree species program.…”
Section: Discussionmentioning
confidence: 99%